Effects of Alternative Feed Timing on Growth Performance and Water Usage in Limit Fed Growing Beef × Dairy Heifers - Clayton H. Stoskopf (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to evaluate the effects of feed delivery time on growth performance and water usage of growing limit-fed heifers during periods of heat stress. Study Description: A total of 257 black-hided dairy-derived beef heifers were blocked by weight, stratified within block, and randomly assigned to 20 pens containing 12 to 13 head/pen. Pens were randomly assigned to one of two treatments: 7:00 a.m. or 7:00 p.m. feed delivery of a diet formulated to provide 60 Mcal of net energy for gain per 100 lb of dry matter (DM) for limited intake. Heifers were fed once daily at 2.0% of body weight (BW) on a DM basis for an 84-day period. Water usage was recorded using meters attached to each water unit. The Bottom Line: Feed timing did not negatively affect growth performance but did reduce water usage when heifers were fed in the evening.
Keywords: feed-timing; growth; water